Drillhole rugosity correction for gamma-gamma density tools – A space modelling approach. Issue 1 (1st December 2019) - Gavriliu, Dragos; Batchelor, James
Summary: This paper describes a novel approach to solving borehole rugosity for single detector gamma-gamma density logging. Modelling the space investigated by the gamma-gamma density tool provides the basis for deriving an applied rugosity correction. This paper also describes how the same correction models when applied to dual density tool detectors can increase the vertical resolution of the tool revealing otherwise hidden formation heterogeneity. Measurements made with single detector gamma-gamma density tools are accurate non-rugose (smooth) boreholes whereas measurements made in rugose (rough) boreholes are typically biased low, due to the undesirable effects of low-density borehole fluid, water or air sitting between the formation and the source or detector and in the path of gamma rays.